Psychometric Properties of Indonesian HEXACO-100: A Facet Level Analysis - Ardi Pratama Sugiarto; Alimatus Sahrah; Anwar Anwar (Jurnal Psikologi, 2022)
The HEXACO personality model is a six-dimensional personality model that is partially independent from the Big Five personality model (Zettler et.al., 2020). Measurement using the HEXACO Personality Inventory-Revised, its sixth dimension, Honesty-Humility, can capture previously unexplored images of personality. This study aims to adapt the HEXACO Personality Inventory-Revised 100 items version (HEXACO-100) into the Indonesian language and examine its psychometric properties. A purposive sample of 605 participants responded to Indonesian HEXACO-100 (67,2% female; mean age: 25,1 years). The result showed that all six factors have good alpha reliability (all factors α > .7), and the exploratory factor analysis and correlation analysis between the dimensions support the validity of the six-dimensional personality model. It can be concluded that this study successfully adapted the HEXACO-100 personality inventory into the Indonesian language, strengthens the existence of a six-dimensional personality model in Indonesia, and underlines that the HEXACO personality inventory is a useful and reliable personality inventory for investigating personality structure in cross-cultural settings.